Roller Bench Design for Measurement of Effective Engine Power - Lakatos, I.; Dely, P. (Acta Technica Jaurinensis, 2014)
Effective performance of road vehicle engines represents an important segment of vehicle specification. A specific measurement method is required for acquisition and assessment of data coming from diagnostic tools attached to the rolling road. A new method has been elaborated by the first author. This method can be used as a measurement system to measure effective engine power for operational diagnostic purposes. Free rollers are needed instead of loading machine, according to the new approach. This article demonstrates the design principles for the roller bench needed.